Study on the Effect of Non-Linear Ventilation Pipe Composite Measures on the Slope Permafrost Subgrade - Zhe Cheng; Zhilong Zhang; Guang Liu; Ying Wu (Sustainability, 2023)
In the alpine mountain area, the stability of the steep-slope permafrost subgrade is mainly affected by the temperature variation in the frozen soil layer at the base of the road. Under the conditions of climate warming and engineering-related disturbance, the cooling of the subgrade is an urgent problem to be solved in the field of construction. In this paper, the numerical calculation method, combined with data monitored in situ, is used to study the cooling effects of several subgrade cooling measures, in which the non-linear ventilation pipe and rubble layer are combined. The results show the following: (1) the temperature field of the steep-slope subgrade is clearly different in lateral terms—after 20 years of operation, the maximum difference in the melting depth between the left shoulder and the subgrade center is 3 m; (2) the maximum melting depth of the gravel subgrade center is 3.85 m, while the maximum difference in the melting depth between the left shoulder and the subgrade center is 2.3 m; (3) the cooling effect of the composite measures is noteworthy, and a −2.2 °C freezing area appears under the subgrade.